Influence of Blood Metabolites on Ovarian Rebound in Postpartum Sahiwal Cows - Uppal, Mithilesh; Awasthi, Manoj Kumar; Poyam, Mahesh Ram; Mishra, Girish Kumar; Verma, Manisha; Parveen, Kaiser (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
Present investigation was carried out to study the influence of blood metabolites, viz., glucose and NEFA on ovarian rebound in postpartum Sahiwal cows. Advance pregnant Sahiwal cows (n=14) maintained at Bull Mother Experimental Farm at Anjora, Durg (CG), India were selected and divided into two Groups, Group I comprised of animals (n=7) with BCS ≥ 2.75 and that of Group II comprised of animals (n=7) with average BCS < 2.75 at one week before parturition. Trans-rectal ultrasound scanning of ovaries was accomplished in animals of both groups on alternate days from 21 to 51 days postpartum to record the development of dominant follicles (DF). Animals of Group-I without DF recorded higher pre-partum BCS than those with DF (n=3). Non-significant differences were recorded in mean serum glucose concentration between animals of Group-I and Group-II during all days of observation. Significant differences were (p<0.01) observed in mean serum glucose concentration between animals with and without DF of Group-I on day 20 postpartum (39.79±0.56 vs 43.53±0.29 mg/dl). Animals (n=3) with DF of Group-I showed significantly increasing trend of mean serum glucose level from 20 to 50 days of postpartum, whereas the animals (n=4) without DF recorded similar serum glucose levels between 10 and 40 days postpartum. Significantly (p <0.05) higher mean serum NEFA concentrations were recorded in animals without DF than in animals with DF of Group-I on all days from the day of calving to 50 days postpartum, except on day 10. It may be concluded that higher serum NEFA concentration influenced the development of dominant follicle in postpartum Sahiwal cows